Trainers’ and Employers’ Perceptions of Training in Intralingual and Interlingual Live Subtitling: A Survey Study - Robert, Isabelle; Iris, Schrijver; Ella, Diels (Journal of Audiovisual Translation, 2019)
Over the past decade, intralingual live subtitling (IntraLS) has become a professional practice backed up by academic research. Interlingual live subtitling (InterLS), in contrast, is still in its infancy. Although the demands for InterLS are growing, a competence profile and a subsequent curriculum design are yet to be developed. The ILSA project aims to bridge this gap by describing the profile of the interlingual live subtitler (InterLS-er) and by developing and validating a training course for this new professional. This article reports on the initial stage of that project: the assessment of the current practice and training of IntraLS and InterLS. Three surveys were disseminated among practitioners, trainers, and broadcasters and service providers. This article focuses on the responses from the latter two groups. The trainers were mainly asked questions about the content of the courses they teach. The employers, i.e. the broadcasters and service providers, were asked about the workflow at their company and the training of their staff members. The responses demonstrate that an all-encompassing training programme for InterLS is still lacking. This finding confirms the idea that research projects like ILSA are needed in order to train future InterLS-ers and to improve future live subtitling.